Investigating the role of the Smoky River watershed on past ice-jam flood regimes at the Peace-Athabasca Delta via analysis of oxbow lake sediment cores - Stratton, Mia Simone (University of Waterloo, 2022)
The Peace-Athabasca Delta (PAD) in northern Alberta has been a focus of concern for decades due to decline in frequency and magnitude of ice-jam floods that sustain ecologically and culturally significant shallow perched lakes. Recent changes to the ice-jam flood regime of the PAD have been attributed to two main stressors, river regulation and climate change, however, the relative influence of each remains a topic of much scientific debate. Hydroelectric regulation of Peace River flow by the W.A.C. Bennett Dam began in 1968 and is widely considered to be the main cause for reduced flooding at the PAD. Longer temporal perspectives provided by paleolimnological records, however, indicate a decline in flood frequency since the early 1900s as a result of climate change. A large proportion of Peace River flow at the time when spring ice-jams floods typically occur is attributed to snowmelt runoff from unregulated ‘trigger tributaries’ including the Smoky and Wabasca rivers. However, our current understanding of the influence of spring discharge from these tributaries on ice-jam flooding and the subsequent recharge of perched basins at the PAD is restricted to the limited hydrometric data available since 1955. To gain a broader temporal perspective of the contribution of the Smoky River to ice-jam flooding at the PAD, sediment cores from two oxbow lakes adjacent to the Little Smoky River were investigated using paleolimnological techniques. Results from loss-on-ignition, x-ray fluorescence, and grain size collectively provide sensitive indicators of shifting flood regimes in the Smoky River watershed during the past ~160-340 years. Temporal variations in flood influence at the Smoky oxbow lakes and paleolimnological records from oxbow lakes in the Wabasca River watershed and at the PAD were characterized by four distinct phases during the past ~340 years. Phases 1 (~1680-1790) and 3 (~1850-1930) were identified as intervals of stronger flood influence while Phases 2 (~1790-1850) and 4 (~1930-2019) were interpreted as ...